2006
DOI: 10.1021/ol0615937
|View full text |Cite
|
Sign up to set email alerts
|

A Retro-Diels−Alder Reaction to Uncover Maleimide-Modified Surfaces on Monolayer-Protected Nanoparticles for Reversible Covalent Assembly

Abstract: Maleimide-modified monolayer-protected gold nanoparticles (MPGN) are prepared from the protected furan-maleimide via the thermally reversible Diels-Adler reaction when required. These maleimide-MPGNs serve as a general platform allowing for a Diels-Alder reaction with furan-modified MPN to prepare larger 3D networks reversibly. [reaction: see text]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
54
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 25 publications
3
54
0
Order By: Relevance
“…Thermally rDA reactions have been used in numerous studies including polymer synthesis [10][11][12][13][14][15][16][17], dendrimers [18][19][20][21], epoxy resins [22][23][24][25], crosslinked polymer networks [26][27][28][29][30], organic-inorganic polymer hybrids [31][32][33], surfactants [34], surface modification [35,36] and remendable selfhealing polymers [37]. Due to the fact that these reactions can proceed under mild conditions without a catalyst, they are attractive for designing covalently reversible bonds with furan and maleimide functional groups which are responsible for association and disassociation [35,37,38]. Polyurethanes are widely used in high resiliency flexible foam seating, rigid foam insulation panels, microcellular foam seals and gaskets, durable elastomeric wheels and tires, automotive suspension bushings, electrical potting components, high performance adhesives, surface coatings and sealants, Spandex fibers, seals, gaskets, carpet underlay, and hard plastic parts (such as for electronic instruments).…”
Section: Introductionmentioning
confidence: 99%
“…Thermally rDA reactions have been used in numerous studies including polymer synthesis [10][11][12][13][14][15][16][17], dendrimers [18][19][20][21], epoxy resins [22][23][24][25], crosslinked polymer networks [26][27][28][29][30], organic-inorganic polymer hybrids [31][32][33], surfactants [34], surface modification [35,36] and remendable selfhealing polymers [37]. Due to the fact that these reactions can proceed under mild conditions without a catalyst, they are attractive for designing covalently reversible bonds with furan and maleimide functional groups which are responsible for association and disassociation [35,37,38]. Polyurethanes are widely used in high resiliency flexible foam seating, rigid foam insulation panels, microcellular foam seals and gaskets, durable elastomeric wheels and tires, automotive suspension bushings, electrical potting components, high performance adhesives, surface coatings and sealants, Spandex fibers, seals, gaskets, carpet underlay, and hard plastic parts (such as for electronic instruments).…”
Section: Introductionmentioning
confidence: 99%
“…Zhu et al [77] reported an approach for the derivatization of monolayer-protected nanoparticle (MPNs) surfaces with a reactive maleimide entity using the thermally reversible DA reaction of furan with a maleimide. These authors showed that by preparing a surface with a furan-maleimide adduct, it is possible to efficiently generate, reversibly, a maleimide-modified MPN via a thermally induced retro-DA reaction.…”
Section: Gold and Metal-based Nanoparticlesmentioning
confidence: 99%
“…23 The same is true for CS, which is a predominant component of the extracellular matrix and meets both structural and biological requirements for biomaterials synthesis. 26 However, to the best of our knowledge, this is the rst time that hybrid hydrogels were prepared by Diels-Alder reaction using Au NPs as cross-linkers for gelatin chains. 24 Additionally, second cross-linking, based on the amide coupling between CS and gelatin was employed to stabilize the hydrogel.…”
Section: Introductionmentioning
confidence: 96%